Educational Objectives for Children in The Qur'an (The Study of Thematic Interpretation) - Three Wulan Ramadhani; Asnil Aidah Ritonga (Universitas Pahlawan Tuanku Tambusai, 2022)
Goal setting is a plan that must be set from the start, otherwise life will be directionless just going with the flow of life. A goal is defined as a direction or goal. Education is an effort that is planned as a human provision in the future. So the purpose of education is important as a predetermined target to go through the educational path so that it will be useful for him later. This study aims to analyze the purpose of education for children in the Qur'an based on the thematic interpretation approach. The results of this study describe that the purpose of Islamic education itself means efforts to obtain results which in the end the goal is to worship only Allah SWT as the main foundation of Islam. The purpose of education is divided into four dimensions, namely the purpose of physical education in the form of physical strength that must be possessed by every individual as a caliph on earth. The purpose of spiritual education is that all human efforts have the ultimate goal of increasing faith in the Creator. The purpose of mind education which means the search for truth in the Qur'an with several stages, namely scientific, empirical, and philosophical. The purpose of social education, which means that the education taken can be useful in all aspects of life, especially for children from elementary age.